Effects of Spartina alterniflora control on soil carbon and nitrogen in coastal wetlands - Xiaoyue Song; Yutong Wang; Baoling Mei; Xitao Zhang; Peng Zheng; Weimin Song; Binbin Tian; Qiqige; Guangxuan Han; Baohua Xie (Watershed Ecology and the Environment)
The invasive species Spartina alterniflora has significantly disrupted the ecological stability of coastal wetland ecosystems. Consequently, its control has become an important aspect of coastal wetland conservation. When controlling S. alterniflora, it is imperative to assess the ecological impacts of control methods. In this study, the effects of different control methods, i.e. “mowing + flooding” (MF) and “mowing + plowing” (MP), on the soil carbon and nitrogen contents in coastal wetlands were investigated in the Yellow River Delta, China. The results showed that the contents of soil organic carbon, inorganic carbon, and total nitrogen in the MF area within 2 years after treatment were 2.03–3.93 g/kg, 13.74–16.06 g/kg, and 0.24–0.47 g/kg, respectively, which were 36.33 %–-199 %, 2.91 %–36.71 % and 115.42 %–212.09 % higher than that those in the CK area, respectively. The C/N ratio in the MF treatment was 6.98–8.54, which was 5.42 %–40.30 % lower than that in the CK treatment. The contents of soil organic carbon, inorganic carbon, and total nitrogen in the MP area were 1.52–2.3 g/kg, 13.07–14.94 g/kg, and 0.2–0.32 g/kg, respectively, which were 15.91 %–54.18 %, 0.97 %–15.56 % and 35.19 %–182.26 % higher than those in the CK area. The C/N ratio in the MP area was 14.72 %–46.79 % lower than that in the CK area. Correlation analysis revealed that the soil carbon and nitrogen contents in the MF area were significantly positively correlated with the soil water content and electrical conductivity, and the C/N ratio was significantly negatively correlated with the soil sand content. In the MP area, the soil carbon and nitrogen contents were affected by the soil water content and electrical conductivity. The soil organic carbon content was also significantly negatively correlated with soil pH and significantly positively correlated with soil clay content. The C/N ratio was significantly negatively correlated with the total nitrogen content. Overall, the effects of MF on the soil carbon and nitrogen content in coastal wetlands were greater than those of MP. Future studies need to pay attention to the changes in tidal hydrological processes to more accurately assess the impacts of the control of S. alterniflora on the overall carbon sink capacity of the intertidal zone.